Controller design and optimization of reactor power control system for ASPWR. (September 2017) - Wan, Jiashuang; Wang, Pengfei; Wu, Shifa; Zhao, Fuyu
Abstract: The objective of this paper is to design a reactor power control system (RPCS) for the advanced small pressurized water reactor (ASPWR) that adopts constant primary loop average coolant temperature and steam generator secondary side steam pressure programs. In this paper, a two-input and two-output linear nuclear steam supply system (NSSS) model is developed first based on the linearization of the nonlinear point reactor core model with one-group delayed neutron and simplified nonlinear once-through steam generator model. Then, both the conventional trial-and-error design method and the improved version of multi-objective, non-dominated sorting genetic algorithm (NSGA-II) are applied for the RPCS controller design. It has been demonstrated by the numerical simulation results that the RPCS control parameters optimized by the NSGA-II provide better control performance than those tuned by conventional design method. Therefore, the NSGA-II based control parameter optimization method is recommended to tune the RPCS controllers.